2007
DOI: 10.1002/mma.937
|View full text |Cite
|
Sign up to set email alerts
|

Solutions through nonclassical potential symmetries for a generalized inhomogeneous nonlinear diffusion equation

Abstract: SUMMARYIn this paper, we consider a class of generalized diffusion equations which are of great interest in mathematical physics. For some of these equations that model fast diffusion, nonclassical and nonclassical potential symmetries are derived. These symmetries allow us to increase the number of solutions. These solutions are unobtainable neither from classical nor from classical potential symmetries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…We can distinguish the following cases: If n v 5 0 by solving (24) and substituting into (25)-(27) leads to generators for which (22) is satisfied, consequently they are nonclassical potential generators and have been considered in [13].…”
Section: Nonclassical Symmetries Of the System (6)mentioning
confidence: 99%
“…We can distinguish the following cases: If n v 5 0 by solving (24) and substituting into (25)-(27) leads to generators for which (22) is satisfied, consequently they are nonclassical potential generators and have been considered in [13].…”
Section: Nonclassical Symmetries Of the System (6)mentioning
confidence: 99%
“…In [21] it also appear in explicit form To obtain nonclassical symmetries of (1.19), we require that the PDE (1.19) and the invariance surface condition…”
Section: From Generatormentioning
confidence: 99%
“…A number of methods relating to symmetry groups have been successfully used to find the exact solutions and symmetry reductions of various special forms and generalized forms of (1.1), including the classical and nonclassical method [7][8][9][10][11][12][13][14][15][16], and the potential and nonclassical potential method [16][17][18][19][20][21][22]. It has been found that the symmetry group methods are effective to classify the equations or to identify the functions in the equations with respect to given symmetries [23,24].…”
Section: Introductionmentioning
confidence: 98%